Elaboration of “cacho de cabra” chilli canned (Capsicum annum L. Var Longum) in three different coverage media - Loyola , Nelson; Acuña , Carlos; Cornejo, Diana; Arriola , Mariela (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The "cacho de cabra" chili pepper (Capsicum annuum L.) is used in the preparation of a wide variety of foods, primarily consumed in dehydrated, raw, or powdered form to flavor and aromatize dishes. To contribute to the development of different types of products using the "cacho de cabra" chili pepper (Capsicum annuum L. var. Longum) as a raw material, a canned version of this chili pepper was developed, considering the covering medium, the amount of NaCl, citric acid, and spices. Three treatments were proposed for this process. The chemical characteristics, sensory attributes, and safety of the manufactured products were evaluated. Analyses of chemical characteristics (sodium content, total acidity, and pH), sensory attributes (color, flavor, aroma, texture, and overall acceptability), and safety (fecal and total coliforms) were performed after 20 and 40 days of storage. Canned goods prepared with treatment T0 (water + 2 % NaCl + citric acid) were the most accepted by the panelists, followed by those prepared with treatment T1 (sunflower oil + spices). Canned goods prepared with treatment T2 (extra virgin olive oil) were not well-received due to their acidic taste and mealy texture. Significant results were found in all three treatments for sodium content, pH, total acidity, and absence of pathogenic microorganisms.